Improving the Mie GACOAN Online Food Ordering Application Using the System Usability Scale (SUS) - Sarungu, Cornelius Mellino; Hatrinidinar Rasya, Raihannissa; Devina Tiara Maharani, Denta; Alfianto, Royan (Universitas Multimedia Nusantara, 2025)
Improvement of the online food ordering application through the System Usability Scale (SUS) method to enhance user satisfaction and streamline the ordering process. Driven by the rapid expansion of online food ordering in Indonesia, this study aims to address long queues and improve customer convenience through optimized digital solutions. Current challenges include delayed ordering processes and limitations in existing application features, such as navigation issues, unclear language, and limited ordering options for dine-in, takeaway, and delivery. The research employs a mixed-methods approach, combining survey and interview data with competitive analysis, to identify critical areas for enhancement. Design improvements focus on user interface (UI) and user experience (UX) to simplify navigation, optimize payment processes, and make language more user-friendly. Initial usability tests resulted in a SUS score of 48, categorizing the application as